The diversity and morphology of the genus Luticola D.G.Mann (Bacillariophyta) from subaerial biofilms of caves in Serbia - Popović, Slađana; Danijela Vidaković; Zlatko Levkov; Olga Jakovljević; Nataša Nikolić; Gordana Subakov Simić; Jelena Krizmanić, (The Research Center of the Slovenian Academy of Sciences and Arts (ZRC SAZU), 2024)
Research of cave-dwelling diatoms is lacking. In these extreme environments, diatoms are restricted to illuminated zones, and are found at the entrance zone and in the lampenflora community. However, the number of identified species is constantly increasing, and new species are being discovered. The genus Luticola is one of the most widely studied genera worldwide and many representatives are characterized as aerophilous and are found in terrestrial habitats. For the first time, Luticola species identified from phototrophic subaerial biofilms of 10 caves in Serbia (cave entrances and lampenflora) based on detailed light microscopy (LM) and scanning electron microscopy (SEM) observations were summarized and discussed. In total 11 representatives of the genus were identified at the species level, and morphological features of Luticola acidoclinata, L. angusta, L. frequentissima, L. dismutica, L. nivalis, L. triundulata, and L. quinquenodis were characterized in detail. For Luticola angusta, electron microscopy images are shown for the first time. Additionally, four new taxa (L. angusta, L. frequentissima, L. kopanjae, and L. poulickovae) were recorded for the diatom flora of Serbia. The study fills an important gap regarding the occurrence and characteristics of Luticola representatives in subaerial habitats.
Keywords: algae, diatoms, Luticola, caves, aerophytic habitats